Aerobic stability in corn silage (Zea maysL.) ensiled with different microbial additives - Bumbieris Junior, Valter Harry; Guimarães, Vinícius André de Pietro; Fortaleza, Ana Paula de Souza; Massaro Junior, Fernando Luiz; Moraes, Gabriella Jorgette de; Meza, Diego Armando Rojas (Acta Scientiarum. Animal Sciences, 2017)
This study aimed to assess different microbial additives, regarding the efficiency of aerobic stability in corn silages. The corn hybrid used for silages production was the DKB 310. The treatments consisted of: 1) control treatment without any microbial additive; 2) Treatment with LPPA composed of: Lactobacillus plantarum CCT 0580 3.1 x 1010 CFU g-1 and Propionibacterium acidipropionici CCT 4843 3.1 x 1010 CFU g-1; 3) Treatment with Inoculum, composed of Bacillus subtilis CCT 0089 3.0 x 109 CFU g-1, Lactobacillus plantarum CCT 0580 1.2 x 1010 CFU g-1 and Propionibacterium acidipropionici CCT 4843 1.5 x 1010 CFU g-1 and 4) Treatment LB, composed only of Lactobacillus buchneri CCT 3746 2.6 x 1010 CFU g-1. The experimental design was completely randomized with five replicates for each treatment. For the parameters evaluated daily, we used the split plot design, in which the different silages were assigned to the plots and the time of exposure to air was assigned to the subplots. There was no difference of additives on silage pH in any of the evaluation days. The control silage reached higher temperatures indicating greater vulnerability. All additives had no aerobic instability. Silages made with the use of microbial additives were effective in maintaining the aerobic stability.